Regulation of Yield in Fir and Spruce Forests of Himachal Pradesh - Raina, V. (Indian Forester, 1962)
The fir and spruce grow in association at an altitude of 8000 and above in Himachal Pradesh. They cover a much larger area than any other conifer in the State. Selection system is applied to these forests. Before the second world war the converted timber was not so popular in the market. The yield was, therefore, uncontrolled. However, in the working plans of the forties mature and over-mature trees by numbers were prescribed for annual removal in a replacement period of 40 years with an additional safeguard. This method has given erroneous results. The actual stem-number distribution is very deficient in lower diameter classes but with a definite preponderance of mature and over-mature trees.